Fiscal and monetary policy interaction during economic shocks: A wedge or bridge for bank profitability? - Jared Osoro; Kiplangat Josea Cheruiyot (Kenya Bankers Association (KBA), 2024)
Persistence of profitability in the Kenyan banking industry masks the limited understanding of the adjustment process of the profit seeking behavior during economic shocks. Whether the adjustment is in response to the adverse outcomes of the shocks, or the inevitable macroeconomic policy response is an open question. This paper seeks to assess the implication of fiscal-monetary interactions on banks' profitability. We deploy both static and dynamic panel models to estimate the influence of the macro policies using bank-level as well as macroeconomic data in Kenya for the period 2003 - 2022. We establish that both monetary policy and fiscal policy matter for bank profitability, their influence revealing the attribute of interconnectivity between the two policies. The banks' profitability is positively influenced by an expansionary fiscal policy, with a similar influence associated with a tightening monetary policy. We contend that for a given set of bankspecific attributes, if monetary and fiscal policies are prominent influencers of profitability, it signals that the banks' reaction function as profit seekers is more a response to policy adjustment to shocks than the underlying economic outcomes. The key inference based on the assessment is that banks' profit seeking attribute while riding on an expansionary fiscal policy and a tightening monetary policy entails risk taking behavior that can potentially push the economy to the boundary of the "region of stability". That puts the spotlight on the attitude of the banks' regulator and that of banks towards profitability and risk-taking and calls for two policy considerations. One is the need for a robust stresstesting framework that takes into account capital adequacy and asset quality optimal thresholds whose breaching we determine to be a possible triggers of market jitters. Two is the necessity of a stable market-based funding mechanism supported by the regulator's liquidity window and complemented by a conservative dividend policy even as profitability may persists. The two policy considerations will potentially obviate a situation where there is a realization that elusive boundaries of "the region of stability" have been breached ex post and the banking system is stable until suddenly it is not.
Keywords: 330; Bank profitability; dynamic panel threshold model; fiscal policy and monetary policy interaction